Substitution of TAG oil with diacylglycerol oil in food items improves the predicted 10 years cardiovascular risk score in healthy, overweight subjects - Telle-Hansen, Vibeke H. (Cambridge University Press, 2012)
Dietary fat is normally in TAG form, but diacylglycerol (DAG) is a natural component of edible oils. Studies have shown that consumption of DAG results in metabolic characteristics that are distinct from those of TAG, which may be beneficial in preventing and managing obesity. The objective of the present study was to investigate if food items in which part of the TAG oil is replaced with DAG oil combined with high α-linolenic acid (ALA) content would influence metabolic markers. A 12-week double-blinded randomised controlled parallel-design study was conducted. The participants (n 23) were healthy, overweight men and women, aged 37–67 years, BMI 27–35 kg/m(2), with waist circumference >94 cm (men) and >88 cm (women). The two groups received 20 g margarine, 11 g mayonnaise and 12 g oil per d, containing either high ALA and sn-1,3-DAG or high ALA and TAG. Substitution of TAG oil with DAG oil in food items for 12 weeks led to an improvement of the predicted 10 years cardiovascular risk score in overweight subjects by non-significantly improving markers of health such as total body fat percentage, trunk fat mass, alanine aminotransferase, systolic blood pressure, γ-glutamyl transferase, alkaline phosphatase and total fat-free mass. This may suggest that replacing TAG oil with DAG oil in healthy, overweight individuals may have beneficial metabolic effects.